Influence of Seed Vigor and Preplant Herbicides on Emergence, Growth, and Yield of Tomato - Argerich, Cosme Alberto; Bradford, Kent J.; Ashton, Floyd M. (American Society for Horticultural Science, 2020)
The interactions of seed vigor with herbicides were studied with respect to seedling emergence, growth, and fruit yield of processing tomatoes (Lycopersicon esculentum Mill. cv. UC204C). Seed vigor (speed of germination) was enhanced by priming in an aerated solution of 0.12 m K2HP O4 plus 0.15 m KN O3 at 20C for 5 days followed by drying in forced air at 30C. The vigor of a second subsample of the same seed lot was reduced by controlled deterioration at 13% water content (dry-weight basis) for 6 days at 50C (aged seeds). Primed, aged, and untreated seeds were tested for their sensitivity to napropamide and metribuzin herbicides in greenhouse and field studies. A seed vigor × herbicide interaction was detected only under greenhouse conditions, where aged seeds were more sensitive than primed or untreated seeds to metribuzin. In April and May field plantings, seed vigor influenced the rate and percentage of final emergence and the earliness of fruit maturity, but had no effect on relative growth rate or total vegetative or reproductive yield. Napropamide at 4.5 and 9 kg·ha-1 and metribuzin at 0.4 and 0.8 kg·ha-1 had no effect on the rate or percentage of seedling emergence, relative growth rate, or total fruit yield. Metribuzin increased the mortality of seedlings at either application rate, and at 0.8 kg·ha-1 delayed early growth and fruit maturity in the April planting. Napropamide treatments did not differ from the water control for all characteristics and environments studied. Chemical names used: 4-amino-6-tert-butyl-3(methylthio)-1,2,4-triazin-5(4H)-one (metribuzin); 2-(α-napthoxy)-N,N-diethyl propionamide (napropamide).